INTERPRETATION OF THE IMAGE OF THE DEER IN ALISHER NAVOI'S GHAZALS (TAMADDUN NURI JURNALI, 2024)
In this article, a large place is devoted to the interpretation of the meaning and essence of such images as deer, goitered gazelle, gazelle, ohu, expressed in the ghazals of Alisher Navoi’s collection “Khazain ul-Maoni”, which he sought to illuminate. We hope that this will help you find the answer to the question to what extent Alisher Navoi used this image in his texts.